Research progress on antiviral drugs and vaccines for severe fever with thrombocytopenia syndrome - Chen, Chendan; Li, Jianhua; Li, Jiaxuan; Huang, Renjin; Chen, Chenghao; Xu, Jinghan; Zhang, Yanjun; Lou, Yongliang (Frontiers in Immunology, 2026)
Severe fever with thrombocytopenia syndrome (SFTS), caused by the SFTS virus (SFTSV), has emerged as a significant global public health threat. Infected patients may present with gastrointestinal, neurological, and cardiovascular ribavirin and favipiravir are currently used in clinical practice, their efficacy remains controversial, and treatment primarily relies on symptomatic and supportive care. To date, there is no standard treatment regimen for SFTSV infection, nor are there any approved vaccines. However, recent advances in SFTSV research and the application of novel technologies have opened new pathways for the development of antiviral drugs and vaccines. This review summarizes the latest progress in the development of therapeutic agents and vaccines against SFTSV, aiming to provide valuable insights for drug development and countermeasure strategies for SFTS.